Bacterial Isolates and Antibiotic Sensitivity Pattern from Urinary Tract Infection in a Private Diagnostic Laboratory in Dhaka, Bangladesh - Rahman, Md Habibur; Ahmed, Md Mushtaque; Sarkar, Dayanidhi; Rahman, Md Asadur (Bangladesh Journal of Microbiology, 2020)
Urinary tract infection (UTI) is a common infection encountered by clinicians and despite the widespread availability of antimicrobial agents, UTI has become difficult to treat because of appearance pathogens with increasing resistance to antimicrobial agents. The objectives of this study were to determine the pathogens causing UTI and to determine the antibiotic sensitivity status among these isolates in a diagnostic laboratory in Dhaka city. A laboratory based cross sectional survey was conducted in a diagnostic Centre in Dhaka Bangladesh from July 2016 to December 2016. A total of 553 urine samples were collected from each patients and processed in microbiology laboratory to isolate pathogens and antibiotic susceptibility test using standard procedure. Among 553 urine samples, 158 (28.57%) samples was found to be culture positive of which 39 (24.70%) were isolated from male patients and 119 (75.30%) from female patients. Escherichia coli (43.67%) were found to be the predominant pathogen followed by Staphylococcus spp. (16.45%), Enterococcus spp. (13.39%), Klebsiella spp. (13.29%), Candida spp. (5.70%), Acinetobacter spp. (4.43%), Pseudomonas spp. (3.80%) and Proteus spp. (1.27%). The carbapenem group antibiotics (imipenem and meropenem) was found to be resistant in 0 to 5.1% of the Gram negative isolates. On the Other hand, most of the Gram positive isolates showed sensitivity to linezolid and vancomycin. This study showed that E. coli isolates were the predominant pathogens and showed resistance to commonly prescribed drugs resulting in a very few options for drug to treat UTIs. Bangladesh J Microbiol, Volume 37 Number 2 December 2020, pp 56-60